Evaluation of the Etiological Factors of Black Tooth Stain in Children - Gülşen İlgen; Dilşah Çoğulu; Ege Uçan; Ataç Uzel (Galenos Yayinevi, 2023)
Aim:Tooth discoloration is a common clinical finding which is considered primarily as an aesthetic problem. Black stain (BS) is a specific type of extrinsic tooth discoloration mostly seen in children, but also in adults and it is not dependent on gender. The present study aimed to investigate the relationships between the presence of BS and dental caries incidence, dental plaque scores and to examine the colonization of Streptococcus mutans, Lactobacillus spp., Actinomyces spp. and Capnocytophaga spp. in dental plaque samples with or without BS. The socioeconomic status of the family, the oral hygiene and dietary habits of the children, and the medical and dental history of the children were also compared between the two groups.Materials and Methods:A total of 1000 children aged 3-12 years were evaluated to take part in this study. From this group, those children with BS (n=44) were selected as the study group. With the same number as the study group, and with a same age and gender profile, 44 children without BS were selected as a control group. Dental examinations including the presence of BS, dental caries incidence and dental plaque scores were performed by the same investigator. Structured questionnaires were completed by the parents. The levels of S. mutans, Lactobacillus spp., Actinomyces spp. and Capnocytophaga spp. were determined from dental plaque samples. All data were analyzed by SPPS 25.0 using Student's t-test, the Mann-Whitney U, Fisher's exact and the chi-squared tests.Results:BS was detected in 4.4% of the patients in the present study. DMFT and DMFS scores were significantly lower in those children with BS than in those without BS (p=0.001 and p=0.010). However, no statistically significant difference was found between dmft and dmfs scores and the presence of BS (p>0.05). Lower numbers of S. mutans and Lactobacillus spp. and greater numbers of Actinomyces spp. and Capnocytophaga spp. were found in those children with BS. There was no statistically significant relationship between S. mutans and Actinomyces spp. and the presence of BS (p>0.05). Colonizations of Lactobacillus spp. were statistically significantly lower, while colonizations of Capnocytophaga spp. were significantly higher in the BS group than in the control group (p<0.05).Conclusion:It could be suggested that the different microbial composition of BS might be associated with lower caries experiences in affected subjects.